Lesions of retrosplenial cortex spare immediate-early gene activity in related limbic regions in the rat. (November 2018) - Powell, Anna L; Hindley, Emma; Nelson, Andrew JD; Davies, Moira; Amin, Eman; Aggleton, John P; Vann, Seralynne D
The retrosplenial cortex forms part of a network of cortical and subcortical structures that have particular importance for spatial learning and navigation in rodents. This study examined how retrosplenial lesions affect activity in this network by visualising the expression of the immediate-early genes c- fos and zif268 after exposure to a novel location. Groups of rats with extensive cytotoxic lesions (areas 29 and 30) and rats with lesions largely confined to area 30 (dysgranular cortex) were compared with their respective control animals for levels of c- fos expression measured by immunohistochemistry. These cortical lesions had very limited effects on distal c- fos activity. Evidence of a restricted reduction in c-fos activity was seen in the septal dentate gyrus (superior blade) but not in other hippocampal and parahippocampal subareas, nor in the anterior cingulate and prelimbic cortices. Related studies examined zif268 activity in those cases with combined area 29 and 30 lesions. The only clear evidence for reduced zif268 activity following retrosplenial cell loss came from the septal CA3 area. The confined impact of retrosplenial tissue loss is notable as, by the same immediate-early gene measures, retrosplenial cortex is itself highly sensitive to damage in related limbic areas, showing a marked c- fos and zif268 hypoactivity across all of its subareas. This asymmetry in covert pathology may help to explain the apparent disparity between the severity of learning deficits after retrosplenial cortex lesions and after lesions in either the hippocampus or the anterior thalamic nuclei.